Evaluation of Bedside Lung Ultrasonography in Diagnosis of Acute Pulmonary Oedema - Tanvir, Sardar Mohammad; Nesa, Fazilatun; Habibullah, Md; Salim, Mohammad; Mohsin, Mohammad; Sarker, Subroto Kumar; Rahman, AKM Ferdous; Khan, Hasib Uddin; Khalil, Md Ibrahim; Hossain, Md Mozaffer (Bangladesh Critical Care Journal, 2024)
Background: Pulmonary oedema is one of the major causes of mortality and morbidity. Acute heart failure is the major cause of pulmonary oedema. NT-pro B-type natriuretic peptide has been found to be effective in distinguishing acute pulmonary oedema from other causes of dyspnea in the emergency care setting. But it is costly and time consuming. Bedside lung ultrasonography (LUS) is being considered as noninvasive, radiation-free and easy to perform tool to diagnosis pulmonary oedema. Objective: To determine the role of bedside LUS in diagnosis of patients with acute pulmonary oedema. Methods: This observational cross-sectional study was carried out in ICU, Department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka from August 2018 to October 2019. Ethical approval was sought before conduction of the study. One hundred critically-ill patients with pulmonary oedema, detected by clinical examination & chest X-ray, due to heart failure were included in the study. Routine labs including NT-pro B-type natriuretic peptide level were sent. Bedside LUS was done with a portable ultrasound machine. Data was collected by using a semi-structured data sheet. Observation and Results: The median age was 42 years (IQR 18-66). Among them, 67.71% were male. 90.0% of patients diagnosed as acute pulmonary oedema by NT-pro B-type natriuretic peptide levels findings and 88.5% of patients were diagnosed as acute pulmonary oedema by bedside lung ultrasonography. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of lung ultrasonography findings alone statistically significant as 94.2%, 66.7%, 96.4% & 54.5% and 91.66% respectively in detection of pulmonary oedema. Conclusions: Bed side lung ultrasonography can be an effective adjunct tool for rapid and high diagnostic accuracy for diagnosis of acute pulmonary oedema along with NT pro BNP level in ICU. Bangladesh Crit Care J September 2024; 12 (2): 113-117